2003
DOI: 10.1074/jbc.m207555200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Epidermal Growth Factor Regulation of Vav2, a Guanine Nucleotide Exchange Factor for Rac

Abstract: Vav2 is a member of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 39 publications
6
78
0
1
Order By: Relevance
“…Vav2 is regulated by tyrosine phosphorylation and/or membrane targeting, but the exact regulatory mechanism is controversial. Vav2 is tyrosine phosphorylated in response to EGF and PDGF signaling and this phosphorylation correlates with enhanced migration of fibroblasts [13,27,46]. However, it is still unclear whether this tyrosine phosphorylation directly regulates Vav2 exchange activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vav2 is regulated by tyrosine phosphorylation and/or membrane targeting, but the exact regulatory mechanism is controversial. Vav2 is tyrosine phosphorylated in response to EGF and PDGF signaling and this phosphorylation correlates with enhanced migration of fibroblasts [13,27,46]. However, it is still unclear whether this tyrosine phosphorylation directly regulates Vav2 exchange activity.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Vav2 is tyrosine phosphorylated in response to EGF and PDGF signaling, and that tyrosine phosphorylation has been associated with Vav2 activation [13,27], we examined the tyrosine phosphorylation of Vav2 following VEGF treatment. We found that Vav2 tyrosine phosphorylation was stimulated by VEGF and peaked at 30 min of VEGF stimulation (Fig.…”
Section: Vav2 Is Tyrosine Phosphorylated In Response To Vegfmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-Tyr-172 Vav2 antibodies were used since EGFR phosphorylates Vav2 at its N-terminal domain, specifically, Tyr-142, Tyr-159, and Tyr-172 (51).…”
Section: Methodsmentioning
confidence: 99%
“…Activation of Rac1 can be mediated by multiple mechanisms, including activation of tyrosine kinase receptors, such as the EGFR (38,51). It has been shown that loss of integrin ␣1␤1 leads to upregulated EGFR tyrosine phosphorylation (39).…”
Section: Fig 7 Ros Partially Contribute To Increased Egfr Phosphorymentioning
confidence: 99%